Virus diseases of cowpea in Africa: IITA Research Guide, No. 53 - Thottappilly, G.; Rossel, H.W. (1996)
Eight viruses are reported from cowpeas in Africa. Cowpea viruses are described from lowland, humid and sub-humid West Africa, as well as from mid-altitude ecological zones mainly found in eastern and southern Africa. Wherever facilities are limited and detailed characterization is not possible, a simple procedure using a combination of serology (agar-gel diffusion test), inoculation to test plants, and vector transmission studies, is proposed for the identification of the cowpea viruses reported so far from Africa. The possibilities of controlling these viruses are briefly discussed.